PERLINDUNGAN ATAS IMIGRAN ROHINGYA DALAM PELANGGARAN HAM BERAT DI MYANMAR DARI ASPEK HUKUM INTERNASIONAL DAN HUKUM NASIONAL - Septiana Tindaon; Abdul Rahman; Chairul Bariah (Journal of USU International Law, 2013)
Abstract Rohingya Ethnic is a minority ethnic in Myanmar and get a serious attention on discrimination to them. Government of Myanmar did not give them nationality status so they did not get the national protection on any hardness to them. Inhumanity treatment to the ethic of Rohingya in Myanmar encourage them to leave their origin nation. They absconding illegaly to other nations ether by land or by sea. Their arrival to the neighbour nations cause the fear to the destination nations. The destination nation assume that the increasing of the number of Rohingya ethnic who arrived in their nation will treat the stability and national defense of their country. The other reason is to put the load to their nation beause there is not a goodwill of Myanmar to solve this problems. The destination nation take any effort to avoid the arrival of the Rohingya ethnic and to take a policy that avoid their arrival. To the ethnic of Rohingnya who arrived in the destination nation, their right is not assured, in which there is not a relocation with health standard. Therefore, it needs efforts of international government to settle this case. The international government must encourage the Myanmar Government to solve this problem immediately, by provide the nationality status to the ethnic of Rohingya for the long term settlement on this case. Government of Myanmar must take a serious action to the crime do by other ethnic in Myanmar to the ethnic of Rohignya or the crime by army of Myanmar to the etnic of Rohingya. Keywords : Human Rights, Refugees, Rohingya